Search for evolutionary roots of land plant arabinogalactan‐proteins in charophytes: presence of a rhamnogalactan‐protein in Spirogyra pratensis (Zygnematophyceae). (26th November 2021) - Pfeifer, Lukas; Utermöhlen, Jon; Happ, Kathrin; Permann, Charlotte; Holzinger, Andreas; von Schwartzenberg, Klaus; Classen, Birgit
SUMMARY: Charophyte green algae (CGA) are assigned to be the closest relatives of land plants and therefore enlighten processes in the colonization of terrestrial habitats. For the transition from water to land, plants needed significant physiological and structural changes, as well as with regard to cell wall composition. Sequential extraction of cell walls of Nitellopsis obtusa (Charophyceae) and Spirogyra pratensis (Zygnematophyceae) offered a comparative overview on cell wall composition of late branching CGA. Because arabinogalactan‐proteins (AGPs) are considered common for all land plant cell walls, we were interested in whether these special glycoproteins are present in CGA. Therefore, we investigated both species with regard to characteristic features of AGPs. In the cell wall of Nitellopsis, no hydroxyproline was present and no AGP was precipitable with the β‐glucosyl Yariv's reagent (βGlcY). By contrast, βGlcY precipitation of the water‐soluble cell wall fraction of Spirogyra yielded a glycoprotein fraction rich in hydroxyproline, indicating the presence of AGPs. Putative AGPs in the cell walls of non‐conjugating Spirogyra filaments, especially in the area of transverse walls, were detected by staining with βGlcY. Labelling increased strongly in generative growth stages, especially during zygospore development. Investigations of the fine structure of the glycan part of βGlcY‐precipitated molecules revealed that the galactan backbone resembled that of AGPs with 1, 3‐ 1, 6‐ and 1, 3, 6‐linked Gal p moieties. Ara f was present only in small amounts and the terminating sugars consisted predominantly of pyranosidic terminal and 1, 3‐linked rhamnose residues. We introduce the term 'rhamnogalactan‐protein' for this special AGP‐modification present in S. pratensis . Significance Statement: Approximately 500 million years ago, land plants evolved in the streptophyte lineage, which required severe changes in cell wall composition, as well as with regard to arabinogalactan‐proteins (AGPs), which are signaling glycoproteins in all land plants. Our investigations on Nitellopsis (Charophyceae) and Spirogyra (Zygnematophyceae) help to determine the evolutionary origin of AGPs in algae and reveal that only Spirogyra contains molecules comparable to land plant AGPs, which possess unique structural modifications, namely rhamnose instead of arabinose (rhamnogalactan‐proteins).